Back Cover: Lyotropic Lamellar Phase Formed from Monolayered θ‐Shaped Carborane‐Cage Amphiphiles (Angew. Chem. Int. Ed. 46/2013). Issue 46 (5th November 2013) - Brusselle, Damien; Bauduin, Pierre; Girard, Luc; Zaulet, Adnana; Viñas, Clara; Teixidor, Francesc; Ly, Isabelle; Diat, Olivier
<x xml:space="preserve">Abstract</x> Unlike the self‐assembly of other surfactants, that of metallacarborane clusters, described as θ‐shaped amphiphiles, does not originate from the hydrophobic effect. In their Communication on page 12114 ff., P. Bauduin et al. show that specific interactions involving many intermolecular dihydrogen bonds, such as CHδ+⋅⋅⋅δ−HB, are the key to understanding the aggregation process in water. This peculiarity results in the formation of lyotropic lamellar phases with a unique monomolecular structure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>